Variables Affecting Young Unemployment in Indonesia - Sari, Sisca Gustina; Dwiputri, Inayati Nuraini; ‎ , Wahjoedi; Parhah, Siti (KnE Social Sciences, 2024)
The successive economic development can be seen from unemployment rate. The percentage of the unemployment rate to the labor force can be seen through the value of the open unemployment rate. From 2016 to 2019, young people have always been the highest contributor to Indonesia’s open unemployment rate. This study discusses the variables that affect the open unemployment rate for rural and urban youth in Indonesia in 2016–2019. The variables are population growth rate, population per capita expenditure, average length of schooling, youth working based on the highest education completed are secondary school, provincial minimum wage, registered job seekers, foreign investment, and gross regional domestic product. This study uses panel data regression method with the Random Effect Model. The results showed that the variable that had a significant effect on the open unemployment rate of rural youth was the gross regional domestic product. Meanwhile, the variables that have a significant effect on the open unemployment rate of urban youth are registered job seekers and foreign investment. Keywords: youth unemployment, rural–urban, random effect model